Efeitos comportamentais do exercício físico em modelo de depressão induzido pela reserpina em peixes-zebra (Danio rerio) - Martins, Gabriela Madalena de Melo (2022)
Major depressive disorder (MDD) has increasingly reached the world population, with an even more expressive increase in recent years due to the COVID-19 pandemic. This clinical condition, which is strongly disabling, is also associated with high mortality, largely due to suicide. Due to this growth and the damage caused by this pathology, studies are needed to identify new alternatives to prevent MDD. In this study, we used adult zebrafish (Danio rerio) as a model to evaluate the effects of reserpine on behavior, neurotransmitter levels, and nucleotide and nucleoside catabolism. To validate the zebrafish model of depression, we used fluoxetine to evaluate its possible reversal role in the locomotor depressive symptoms caused by reserpine. In addition, we evaluated the influence of physical exercise and its preventive role on the behavior of animals exposed to reserpine. Firstly, the animals were exposed to reserpine at a dose of 40 μg/mL for 20 minutes and, after 7 days, neurochemical, behavioral, and memory analyzes were performed. We observed an increase in immobile time and in the time spent in the bottom zone of the tank. In addition, a decrease in the distance traveled and velocity was observed. However, the data showed no changes in the memory and social interaction of these animals. Afterward, serotonin, dopamine and the metabolite DOPAC levels were analyzed. We observed a significant reduction of these neurotransmitters and an increase in the metabolite levels. The activities of nucleoside triphosphate diphosphohydrolase, ecto-5'-nucleotidase and adenosine deaminase (ADA), enzymes involved in the control of nucleotide and nucleoside levels, were also evaluated in brain membranes of zebrafish exposed to reserpine. The results demonstrated a significant increase in the ADP hydrolysis and a reduction in AMP hydrolysis and ecto-ADA activity. To assess if the behavioral changes promoted by reserpine could be modulated by antidepressant drugs and thus validate the zebrafish-depression model induced by this drug, the animals were chronically exposed to fluoxetine (7 days), a drug whose action is widely known for the treatment of MDD, where the reversal of the behavioral changes caused by reserpine was observed, establishing this model of depression. To investigate the effect of physical exercise, the animals were submitted to physical exercise for 6 weeks as a way of preventing the effects of reserpine. The results demonstrated the protection of physical exercise against the behavioral effects caused by reserpine in zebrafish. Our results showed that reserpine was effective for the induction of MDD symptoms in this animal model, and physical exercise may be an alternative to prevent the effects induced by reserpine.